2018
DOI: 10.2147/dddt.s166330
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring antiangiogenesis of bevacizumab in zebrafish

Abstract: Bevacizumab, which is a humanized anti-VEGF antibody, has been successfully applied in clinics since 2004. Bevacizumab in combination with chemotherapy showed high safety and has been applied to solid tumors. However, studies on the insight into the mechanism about the antiangiogenesis activity of bevacizumab were mostly done on mice models, and so there are no visual and intuitive models to observe the process of antiangiogenesis. Here, we first used a zebrafish model to investigate the angiogenesis suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
(41 reference statements)
1
12
0
Order By: Relevance
“…It starts as early as 30 hpf with the migration of cells from the posterior cardinal vein (PCV), and it is completed by 72 hpf with the formation of a complete SIV basket connected with intercapillary branches. Changes in the formation of this structure represent a typical readout for treatments with pro or anti-angiogenic effects [ 8 , 9 ]. Recently, experimental approaches, such as zebrafish yolk membrane (ZFYM) angiogenesis assay and tumor xenotransplantation (TX) assays [ 10 , 11 ], have been developed to exploit the potential of SIVP for the study of the impact of small molecules and growth factors on developmental vascularization.…”
Section: Introductionmentioning
confidence: 99%
“…It starts as early as 30 hpf with the migration of cells from the posterior cardinal vein (PCV), and it is completed by 72 hpf with the formation of a complete SIV basket connected with intercapillary branches. Changes in the formation of this structure represent a typical readout for treatments with pro or anti-angiogenic effects [ 8 , 9 ]. Recently, experimental approaches, such as zebrafish yolk membrane (ZFYM) angiogenesis assay and tumor xenotransplantation (TX) assays [ 10 , 11 ], have been developed to exploit the potential of SIVP for the study of the impact of small molecules and growth factors on developmental vascularization.…”
Section: Introductionmentioning
confidence: 99%
“…According to our knowledge, this is the first study investigating the linker effect on scFv antibodies by using a zebrafish model. Zebrafish SIV development is induced by VEGF, and previous studies showed that human anti-VEGF antibodies can inhibit this process 38 . Due to the transparency of the zebrafish and, the robustness of the embryo and larvae for micromanipulation, zebrafish is an advantageous model for in vivo testing of anti-VEGF antibodies 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Several anti-angiogenic agents have been successfully tested in zebrafish [ 48 ]. Zebrafish embryos are permeable to small molecules, which can be dissolved in their culture medium; moreover, it is well known that some aspects of the physiological development of the sub-intestinal vein (SIV) and intersomitic and retinal vessels can simulate tumor-induced angiogenesis and be an important platform to test and quantify the effect of anti-angiogenic compounds [ 49 ]. Moreover, a zebrafish tumor-xenograft is a suitable platform to study neovascularization occurring with cancer progression in live animals.…”
Section: Discussionmentioning
confidence: 99%